(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: The objectives of this study were to compare the graft uptake and post-operative hearing results of underlay myringoplasty with temporalis fascia and perichondrial-cartilage composite graft in high risk perforations. Materials & Methods: Patients of ages of 13 years and above with diagnosis of chronic otitis media – mucosal type with high risk perforations undergoing myringoplasty were included. Criteria of high risk were >50% perforation of tympanic membrane, revision cases, absent/eroded handle of malleus, oedematous/unhealthy middle ear mucosa and marginal perforation of any size. Pure tone audiometry was done within 1 week before surgery. Seventy cases included for myringoplasty were randomly allocated by lottery method into two groups with 35 cases each in temporalis fascia group and perichondrial - cartilage composite graft group. After 6 weeks graft uptake results were assessed and post-operative hearing was evaluated and compared within and between the groups. Results: Graft uptake rates in temporalis fascia group and perichodrial - cartilage composite graft group were 88.57% and 91.43%, respectively with no statistically significant difference between the groups (p = 0.69). The mean pre- and post-operative air bone gaps in temporalis fascia group were 31.81 ± 10.49 dB and 17.87 ± 7.96 dB. The mean pre- and post-operative air bone gaps in perichondrial - cartilage composite group were 35.19 ±7.26 dB and 22.62 ± 8.77 dB. These differences in both the groups were statistically highly significant (p < 0.001) showing improvement in the hearing after surgery. The mean post-operative ABG gains were 13.94 ± 8.36 dB and 12.57 ± 8.21 dB in temporalis fascia and perichondrial - cartilage composite groups respectively. Conclusion: The graft uptake rates and hearing results after perichondrial - cartilage composite graft are similar to those of temporalis fascia graft. Perichondrial- cartilage composite graft even though more rigid and thicker than temporalis fascia did not affect post-operative hearing results adversely